PEDAGOGICAL FEATURES OF USING PSYCHOLOGICAL TECHNIQUES AND METHODS IN THE EDUCATIONAL ENVIRONMENT - Polatova Tatyana Djalalitdinovna (Western European Studies, 2025)
This article examines the pedagogical aspects of using psychological techniques and approaches in a modern educational environment. It analyzes the didactic conditions that determine the selection and effectiveness of psychological methods. Particular attention is paid to the classification of the pedagogical functions of psychological techniques. The paper also identifies the potential risks and limitations associated with the inappropriate use of psychological techniques and emphasizes the role of teacher training
Keywords: psychological techniques; pedagogical conditions; educational environment